Use Of Metaphors in the Work of Shavkat Rahmon - Durdona Yunusova Akhmatovna (Genius Journals, 2022)
This article discusses the role of metaphors used in the work of Shavkat Rahmon, the creation of dissimilar syntactic figures, syntactic and stylistic combinations
Keywords: Metaphor; linguistic; pragmatic; syntactic-stylistic combination